The benefits of influenza vaccination in patients with cardiovascular disease: a systematic review and meta-analysis - Wei, Meng; Liu, Lei; Zhou, Kaiyu; Li, Yifei (Frontiers in Pharmacology, 2026)
BackgroundThe clinical impact of high-dose influenza vaccination on cardiovascular outcomes in patients with established cardiovascular disease (CVD) remains controversial. To this end, our study aimed to assess the impact of influenza and high-dose influenza vaccine on cardiovascular outcomes in patients with CVD or at high risk for CVD.MethodsWe systematically searched three electronic databases from construction to 5 November 2025. The data extraction and meta-analysis were conducted following PRISMA workflow, utilizing both fixed- and random-effects models to ensure robust statistical analysis. The primary clinical outcomes included all-cause mortality (ACM) and major adverse clinical events (MACEs). Secondary endpoints included all-cause hospitalization (ACH), cardiovascular mortality (CVM), heart failure (HF), myocardial infarction (MI), stroke, ICU admission, and non-cardiovascular death.ResultsA total of 36 studies were included for this research. According to the scope of the research, hierarchical analyses were performed among several subgroups. For efficacy evaluation, we included 25 articles, with a total of 869,795 vaccinated and 1,306,470 unvaccinated participants. Influenza vaccination was associated with a significant reduction in ACM (OR = 0.74; 95% CI, 0.60–0.91), MACE (OR = 0.62; 95% CI, 0.46–0.83), and ICU admission (OR = 0.33; 95% CI, 0.22–0.49) compared to those in the control group. Influenza vaccine only provided a significant prevention of CVM (OR = 0.59; 95% CI, 0.39–0.89) and ACH (OR = 0.80; 95% CI, 0.74–0.87) among established CVD patients. No significant advantage of influenza vaccine in reducing the incidence of HF, non-cardiovascular death, MI, and stroke was observed. Then we also evaluated the efficacy of high-dose vaccination strategy in CVD management. Eleven studies were included for this purpose, and the pooled outcome analysis demonstrated that the high-dose strategy did not provide any benefit in reducing ACM and MACE.ConclusionThe influenza vaccination provided significant benefits in reducing ACM and MACE. However, it failed to demonstrate advantage in managing HF, MI, and non-cardiovascular death in patients with CVD. Additionally, the high-dose influenza vaccination strategy did not present efficacy in preventing adverse outcomes of CVD compared to the standard strategy.